Validating an instrument to investigate students’ conception of Salt hydrolysis - Isnatul Husniah; Habiddin Habiddin; Muhammad Sua’idy; Nuryono Nuryono (Journal of Disruptive Learning Innovation (JODLI), 2019)
This paper outlines the development and validation of a Four-tier instrument in the topic of salt hydrolysis (FTISH). The instrument was developed by using the procedure of FTDICK instrument as published by Habiddin & Page (2019). This study was a part of other separates studies conducted by other groups of researchers including Devita, Habiddin & Suaidy (2019) (in press). This study involved 127 students in total and data collection were carried out two times involving 64 students in the first data collection and 63 students in the second one. The participants of both groups were public secondary school students from Malang. The FTISH consists of 23 questions. The results show that the validity of the questions ranged between 0.263 and 0.745. The reliability of the instrument was 0.80 and falls in the high category. The future implementation of the instrument to support the teaching and learning of salt hydrolysis are also discussed.